If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = 4(6g + -12) + -2y Reorder the terms: -4 = 4(-12 + 6g) + -2y -4 = (-12 * 4 + 6g * 4) + -2y -4 = (-48 + 24g) + -2y Solving -4 = -48 + 24g + -2y Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-24g' to each side of the equation. -4 + -24g = -48 + 24g + -24g + -2y Combine like terms: 24g + -24g = 0 -4 + -24g = -48 + 0 + -2y -4 + -24g = -48 + -2y Add '4' to each side of the equation. -4 + 4 + -24g = -48 + 4 + -2y Combine like terms: -4 + 4 = 0 0 + -24g = -48 + 4 + -2y -24g = -48 + 4 + -2y Combine like terms: -48 + 4 = -44 -24g = -44 + -2y Divide each side by '-24'. g = 1.833333333 + 0.08333333333y Simplifying g = 1.833333333 + 0.08333333333y
| 6-3x+2x=9x+26 | | .6x+22=28 | | -(4)(-2)= | | 3x-10=x+8 | | 3a-12b=x | | .5b=3 | | R=-6.25x^2+75x+1000 | | 0.55b=3 | | 3x-8=6x+8 | | -(10)= | | 14=5x-4x+8 | | .5x-29=-22 | | 8-3x=4+x | | 2p+22=-6p | | x+24=10 | | -(-9)= | | 32=0.6x+-34 | | (3w+5)(w+1)= | | -8a=5a+2a | | 7+7x+3x=-93 | | 6=12+4y | | (2)+4x=(2)+36-5x | | (2)4x=(2)36-5x | | (x)/(3)-4=8 | | -3(r+5)=-41 | | 3x+24=5x+4 | | 2(5x-1)-(7x-5)=8-(3x+2) | | 2x^3+7x^2+2x-3=0 | | .2x+27=22 | | 3x+2x-4=21 | | -(2)(-5)= | | -5(2y-3)=3(1-4y)+13 |